Is Poland still attractive for foreign investments? - Magdalena Jasiniak (e-Finanse: Financial Internet Quarterly, 2015)
Since the economic transition Poland has faced many changes. Accession to the European Union improved the Polish economy and made it more attractive for foreign investments. Since 2004 Poland has been one of the major destinations of FDI in East and Central Europe Countries. Also during the global economic crisis Poland was a good location for foreign capital. The main aim of this article is an attempt to assess whether Poland is still attractive for the location of foreign direct investment. This article is a preliminary study. It is based on statistical analysis describing changes in foreign capital flows in Poland and its position in relation to other European Union countries. Results show that the position of Poland on the map of foreign investment has dramatically changed.
Keywords: F21; F23; E32; 330; foreign direct investment; economic crisis; globalization